2015
DOI: 10.15171/ijhpm.2015.191
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Primary Healthcare Provider Choice Among Insured Persons in Ashanti Region, Ghana

Abstract: Background: In early 2012, National Health Insurance Scheme (NHIS) members in Ashanti Region were allowed to choose their own primary healthcare providers. This paper investigates the factors that enrolees in the Ashanti Region considered in choosing preferred primary healthcare providers (PPPs) and direction of association of such factors with the choice of PPP. Methods: Using a cross-sectional study design, the study sampled 600 NHIS enrolees in Kumasi Metro area and Kwabre East district. The sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Following Grossman [16], Amaghionyeodiwe [27], and Boachie [20], we assume that the utility of a hypertensive patient depends on the consumption of two goods: good health (H); and consumption of all other goods and services (X). S represents the social and economic characteristics of the patient.…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Following Grossman [16], Amaghionyeodiwe [27], and Boachie [20], we assume that the utility of a hypertensive patient depends on the consumption of two goods: good health (H); and consumption of all other goods and services (X). S represents the social and economic characteristics of the patient.…”
Section: The Modelmentioning
confidence: 99%
“…The study employs descriptive and inferential statistics to analyze the data. As in Dou et al [3] and Boachie [20], percentages are used to obtain the differences in responses and background information. To ascertain the effect of socio-economic and demographic variables on outpatient healthcare utilization, we employed logistic regression model.…”
Section: Sources Of Data and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Amaghionyeodiwe (2008) revealed among other findings that, monetary prices and distance from the facility decreased the choice of using modern healthcare providers in Nigeria. Specifically on Ghana, Boachie (2016) in the Kumasi metropolis and Kwabre East District of Ghana found additional charges, income, age, clean environment, reputation, availability of drugs, waiting time, availability of doctors, residence and gender to influence the choice of preferred health care providers for enrolees under the Ghana National Health Insurance scheme. Fenny, Asante, Enemark and Hansen (2015) in three Districts of Ghana among other findings, revealed that having a health insurance increased the choice of formal care over informal healthcare.…”
Section: Literature Reviewmentioning
confidence: 99%